Atención integral a adultos mayores en situación de abandono en el Hogar de ancianos “Dr. Hugo Agila Vargas” del cantón Paltas en la actualidad. - Vivanco Mocha, Verónica Johanna (2024)
Abandonment of older adults is a phenomenon that reflects a series of failures in the social and family structure. This neglect can be physical, emotional, financial, or a combination of these. Homes for the elderly often become the last resort for these individuals, who arrive with complex and multifaceted needs due to their old age. The main objective of this research study was to analyze the causes and consequences of the abandonment of the elderly in the Dr. Hugo Agila Vargas home for the elderly at present, in order to propose improvements for comprehensive care. The methodology used corresponds to the socio-critical paradigm and with a qualitative approach, which allowed me not only to understand and document the situation of neglect of older adults, but also to propose significant changes to improve their care and quality of life. The study population consisted of 13 older adults and four of the home's caregivers. It should also be noted that data collection was done through participant observation of the older adults and interviews with the caregivers. The results indicate that critical problems such as social isolation on the part of the family generate a profound feeling of abandonment in the older adult, which in turn can trigger a mental disorder such as depression, experiencing sadness and loneliness. In addition, the lack of resources and lack of specialized personnel in different areas, is a fundamental aspect to develop strategies to improve the comprehensive care of the residents of the nursing home “Dr. Hugo Agila Vargas” in the Canton Paltas.